Costs of resistance in insect-parasite and insect-parasitoid interactions. - Kraaijeveld, A; Ferrari, J; Godfray, H (2002)
Most, if not all, organisms face attack by natural enemies and will be selected to evolve some form of defence. Resistance may have costs as well as its obvious benefits. These costs may be associated with actual defence or with the maintenance of the defensive machinery irrespective of whether a challenge occurs. In this paper, the evidence for costs of resistance in insect-parasite and insect-parasitoid systems is reviewed, with emphasis on two host-parasitoid systems, based on Drosophila melanogaster and pea aphids as hosts. Data from true insect-parasite systems mainly concern the costs of actual defence; evidence for the costs of standing defences is mostly circumstantial. In pea aphids, the costs of standing defences have so far proved elusive. Resistance amongst clones is not correlated with life-time fecundity, whether measured on good or poor quality plants. Successful defence by a D. melanogaster larva results in a reduction in adult size and fecundity and an increased susceptibility to pupal parasitoids. Costs of standing defences are a reduction in larval competitive ability though these costs only become important when food is limited. It is concluded that costs of resistance can play a pivotal role in the evolutionary and population dynamic interactions between hosts and their parasites.